Association between characteristics of nursing teams and patients' aggressive behavior in closed psychiatric wards. Issue 4 (3rd May 2022) - Doedens, Paul; Vermeulen, Jentien; ter Riet, Gerben; Boyette, Lindy‐Lou; Latour, Corine; de Haan, Lieuwe
Abstract: Purpose: Estimate the effect of nursing, shift, and patient characteristics on patients' aggression. Design and Methods: Follow‐up study on a closed psychiatric ward was performed to estimate the effect of nursing team characteristics and patient characteristics on the incidence of aggression. Findings: The incidence of aggression ( n = 802 in sample) was lower in teams with >75% male nurses. Teams scoring high on extraversion experienced more verbal aggression and teams scoring high on neuroticism experienced more physical aggression. Younger patients and/or involuntarily admitted patients were more frequently aggressive. Practice Implications: These findings could stimulate support for nurses to prevent aggression.